Tinjauan Analitik dan Kritik: Konsep dan Praktik Multi Level Marketing (MLM) Syari’ah di Indonesia - Mufti Afif; Richa Angkita Mulyawisdawati (Cakrawala: Jurnal Studi Islam, 2018)
To obtain an expected benefit and avoid the business risk, effective and efficient management is needed. In general, Multi Level Marketing (MLM) system in Indonesia is still considered quite role in driving the economy. Even though in some cases, this MLM system is often used as a cover for Money Game businesses that deify passive income. So that, the conversations about it often reap the pros and cons of some business people. MUI itself issued DSN fatwa No. 75/DSN/MUI/VII/2009 concerning sharia MLM. It means that MUI issues a fatwa to allow the MLM system if required the terms and conditions. The research used a library approach, where studies of MLM systems spread across several sources of books and scientific articles are reviewed and then conclusions are taken. The results of the study are the MLM system has less benefits than the problem. MLM system has positive values, including: 1) easy marketing / distribution of products; 2) marketing costs is lower, and 3) there are bonuses that make motivation for MLM members to develop their business. The madharat caused by the MLM system is that there is a lot of confusion that causes the marketing system to be out of order